Ethanolamine-induced assembly of microcompartments is required for Fusobacterium nucleatum virulence - Dana S. Franklin; Yi-Wei Chen; Yimin Chen; Manuel Wittchen; Angela Agnew; Alexis Luu; Julian P. Whitelegge; Z. Hong Zhou; Andreas Tauch; Asis Das; Hung Ton-That (mBio)
ABSTRACT Many bacteria metabolize ethanolamine as a nutrient source through cytoplasmic organelles named bacterial microcompartments (BMCs). Here we investigated the molecular assembly, regulation, and function of BMCs in Fusobacterium nucleatum—a Gram-negative oral pathobiont that is associated with adverse pregnancy outcomes. The F. nucleatum genome harbors a conserved ethanolamine utilization (eut) locus with 21 genes that encode several putative BMC shell proteins and a two-component signal transduction system (TCS), in addition to the enzymes for ethanolamine transport and catabolism. We show that the expression of most of these genes and BMC formation are highly increased in wild-type fusobacteria when cultured in the presence of ethanolamine as a nutrient source. Deletion of the response regulator EutV eliminated this induction of eut mRNAs and BMCs, thus demonstrating that BMC formation is transcriptionally regulated by the TCS EutV-EutW in response to ethanolamine. Mass spectrometry of isolated BMCs unveiled the identity of the constituent proteins EutL, EutM1, EutM2, and EutN. Consistent with the role of these proteins in BMC assembly and metabolism, deletion of eutN, eutL/eutM1/eutM2, or eutL/eutM1/eutM2/eutN not only affected BMC formation but also ethanolamine utilization, causing cell growth defects with ethanolamine as a nutrient. BMCs are also assembled in fusobacteria cultured with placental cells or the culture media, a process that is dependent on the BMC shell proteins. Significantly, we show that the eutN mutant is defective in inducing preterm birth in a mouse model. Together, these results establish that the BMC-mediated metabolism of ethanolamine is critical for fusobacterial virulence.IMPORTANCEThe oral anaerobe Fusobacterium nucleatum can spread to distal internal organs, such as the colon and placenta, thereby promoting the development of colorectal cancer and inducing preterm birth, respectively. Yet, how this opportunistic pathogen adapts to the various metabolically distinct host cellular niches remains poorly understood. We demonstrated here that this microbe assembles specialized metabolic organelles, termed bacterial microcompartments (BMCs), to utilize environmental ethanolamine (EA) as a key environmental nutrient source. The formation of F. nucleatum BMCs, containing BMC shell proteins EutLM1M2N, is controlled by a two-component system, EutV-EutW, responsive to EA. Significantly, this ability of F. nucleatum to form BMCs in response to EA is crucial for its pathogenicity evidenced by the fact that the genetic disruption of BMC formation reduces fusobacterial virulence in a mouse model of preterm birth.